Myocardial work index as a marker for physiologic cardiac remodeling in elite endurance athletes - Di Gioia, G.; Ferrera, A.; Ortolina, D.; Pelliccia, A.; Squeo, M. R. (International Journal of Cardiology, 2026)
Introduction Endurance athletes are expected to present a cardiac remodeling characterized by eccentric hypertrophy. Differentiation from underlying cardiomyopathy mimicking a similar cardiac remodeling may be challenging. Myocardial work indexes (MWI) have been shown to be useful in distinguishing between physiological adaption and pathological changes in the athletes' heart. However, data on MWI in athletes are scarce. The aim our study is to describe MWI in a cohort of endurance athletes.